IMPLEMENTASI SISTEM ABSENSI BIOMETRIK MAHASISWA TERINTEGRASI DATA KEHADIRAN SIMAK DOSEN MENGGUNAKAN MIKROKONTROLER ESP32 - Muh Tino Kabarak Ballagi; Muhammad Akbar Yasin; Zila Razilu (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2025)
Attendance is one of the important aspects of human resource management in various institutions, whether in the educational environment, companies, or government agencies. Biometrics is a technology used to identify or verify a person's identity based on unique physical or behavioral characteristics. The system development method used in this research is the prototype method. This research produces a biometric attendance tool using the ESP32 microcontroller integrated with the Simak system for UM Kendari, which can then be implemented according to its function. With the presence of this biometric attendance tool, it is hoped that it can minimize any potential cheating that may occur in the lecture attendance process and make it easier for lecturers to manage student attendance. The results of the testing of this biometric attendance system and tool were successfully conducted, marked by the tool functioning well and the system being able to integrate with the lecturer's Simak. The fingerprint testing of students was conducted on 30 people with an average of 3 trials each, where 27 people were successfully detected and the remaining 3 failed to be detected due to the condition of the students' fingers being injured.